When Do Coworkers’ Idiosyncratic Deals Trigger Social Undermining?—The Moderating Roles of Core Self-Evaluations and Conscientiousness - Wang, Jingwen; Ma, Jun (Frontiers in Psychology, 2022)
Idiosyncratic deals are personalized work arrangements negotiated between enterprises and employees based on employees' abilities and needs, previous studies have focused more on their positive effects on i-dealers and neglected the negative effects on peers in the process of interpersonal interaction. In view of this, this study explores the effects of coworkers’ idiosyncratic deals on employees' social undermining and the internal mechanism based on social comparison theory. This study tested the theoretical model with a sample of 331 employees from six enterprises in China. The results showed that the interaction between perceptions of coworkers’ receiving idiosyncratic deals and low core self-evaluations stimulated employees' feelings of relative deprivation, which triggered social undermining toward i-dealers. At the same time, employees' conscientiousness could weaken the positive effect of relative deprivation on social undermining. Therefore, it reveals the negative peer effect of idiosyncratic deals, and provides theoretical and practical implications for preventing the interpersonal harm doing caused by idiosyncratic deals.